2018
DOI: 10.1038/s41598-018-31589-x
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering evolutionary dynamics of SWEET genes in diverse plant lineages

Abstract: SWEET/MtN3/saliva genes are prevalent in cellular organisms and play diverse roles in plants. These genes are widely considered as evolutionarily conserved genes, which is inconsistent with their extensive expansion and functional diversity. In this study, SWEET genes were identified from 31 representative plant species, and exhibited remarkable expansion and diversification ranging from aquatic to land plants. Duplication detection indicated that the sharp increase in the number of SWEET genes in higher plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
0
32
0
Order By: Relevance
“…In this study, we identified 25 SWEET genes in the genome of M. truncatula , and the number was comparable to that in various plant species, such as Arabidopsis (17 genes) [1,2], cucumber (17 genes) [5,35], rice (21 genes) [30], sorghum (23 genes) [34], banana (25 genes) [32], tomato (29 genes) [32], cabbage (30 genes) [43], potato (35 genes) [33], and rubber tree (36 genes) [36]. Gene duplication, including tandem and segmental duplication events, can be a crucial factor that affects plant genome evolution [56,57], and contributes to the expansion of SWEET gene family in various plant species [12,58]. For example, two and seven pairs of tandemly duplicated genes were detected in cucumber and cotton, respectively [35,59].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we identified 25 SWEET genes in the genome of M. truncatula , and the number was comparable to that in various plant species, such as Arabidopsis (17 genes) [1,2], cucumber (17 genes) [5,35], rice (21 genes) [30], sorghum (23 genes) [34], banana (25 genes) [32], tomato (29 genes) [32], cabbage (30 genes) [43], potato (35 genes) [33], and rubber tree (36 genes) [36]. Gene duplication, including tandem and segmental duplication events, can be a crucial factor that affects plant genome evolution [56,57], and contributes to the expansion of SWEET gene family in various plant species [12,58]. For example, two and seven pairs of tandemly duplicated genes were detected in cucumber and cotton, respectively [35,59].…”
Section: Discussionmentioning
confidence: 99%
“…According to Eom et al [35] and Li et al [36], 24 genes comprise the SWEET family in maize. All putative maize SWEET proteins possess two MtN3/saliva domains, and most are predicted to have the seven transmembrane helices typical of SWEET transporters, except for ZmSWEET4a and ZmSWEET6a, which are predicted to have six helices (Figure S4).…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that SWEET members are grouped in four clades [35,36,37]. Maize SWEETs are distributed among the four clades, but most fall into clade III, which also groups most of the SWEET transporters from A. thaliana and rice.…”
Section: Resultsmentioning
confidence: 99%
“…Most of these genes went through a purifying selection during evolution, a process that selectively removes the deleterious alleles (Li et al, 2018). Besides, the significantly large number of SWEET genes in higher plants was attributed to the presence of segmental and tandem duplications in comparison to the lower land plants (Li et al, 2018). Based on the phylogenetic distribution, SWEET transporters are grouped into four clades (Chandran, 2015).…”
Section: Sweet Family Transportersmentioning
confidence: 99%
“…In sweet potato, Fusarium oxysporum inflicts huge commercial losses to the farmers. The SWEET gene IbSWEET10 conferred resistance to Fusarium wilt and characterized using RNAi (RNA interference) approach (Li et al, 2018). Besides bacterial and fungal pathogens, the role of SWEET genes in viral disease resistance has also been reported.…”
Section: Sweet Family Transportersmentioning
confidence: 99%